STUDI KASUS : PENGARUH PEMBERIAN BUAH BIT TERHADAP KADAR HEMOGLOBIN PADA IBU HAMIL DENGAN ANEMIA - Meilan, Nessi (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2023)
Pregnancy is a period of fetal growth and development, so nutritional disorders that occur during pregnancy have a major impact on the health of the mother and fetus. One of the nutritional problems that can occur in pregnant women is anemia. Anemia is a condition when the body lacks healthy red blood cells or when red blood cells do not function properly, leading to reduced oxygen flow to the body's organs. Non-pharmaceutical approach handling anemia is consuming beetroots wich contain rich nutrients such as folic acid, vitamin C and beets also contain relatively sufficient iron so that it can overcome anemia caused by iron deficiency. The purpose of this study was to obtain an overview of the effect of beetroot on Hemoglobin levels in pregnant women. The research method uses a case study design, the research location is in Pondok Udik Village, Bogor Regency in February-March 2022. Samples of the reseach was 2 pregnant women, with sampling techniques using purposive sampling techniques. The instruments used are digital Hb checking tools, consubeetroot juice, how to make beet juice, how to store beet juice, how to consume beet juice, checklist for consuming beet juice and questionnaires. The results of this study showed that there was an increase in Hb levels in both respondents after consuming beets. The conclusion from the evaluation results of the two respondents was that Hb levels increased by an average of 0.8 g / dl per week after routine and scheduled beet feeding. Consumption of beetroots is highly recommended by pregnant women in the trimester two to prevent anemia. Keywords : Anemia, pregnant women, beetroot